Pest Control in Vegetable Gardens - Tisserat, Ned A.; Bauernfeind, Robert J. (My University, 2003)
This publication is for home gardeners who deal with pest control in their vegetable gardens. It has detailed descriptions of the pest types and how to remove them.
C595_2003_05
Keywords: C595; Lawn and Garden; Insects; C